Design of Optical‐Imaging Probes by Screening of Diverse Substrate Libraries Directly in Disease‐Tissue Extracts. (26th August 2020) - Tholen, Martina; Yim, Joshua J.; Groborz, Katarzyna; Yoo, Euna; Martin, Brock A.; van den Berg, Nynke S.; Drag, Marcin; Bogyo, Matthew
Abstract: Fluorescently quenched probes that are specifically activated in the cancer microenvironment have great potential application for diagnosis, early detection, and surgical guidance. These probes are often designed to target specific enzymes associated with diseases by direct optimization using single purified enzymes. However, this can result in painstaking chemistry efforts to produce a probe with suboptimal performance when applied in vivo. We describe here an alternate, unbiased activity‐profiling approach in which whole tissue extracts are used to directly identify optimal peptide sequences for probe design. Screening of tumor extracts with a hybrid combinatorial substrate library (HyCoSuL) identified a combination of natural and non‐natural amino‐acid residues that was used to generate highly efficient tumor‐specific probes. This new strategy simplifies and enhances the process of probe optimization without any a priori knowledge of enzyme targets and has the potential to be applied to diverse disease states using clinical or animal‐model tissue samples. Abstract : Proteolytic profiling of disease‐tissue lysates using highly diverse substrate libraries enables a streamlined development of in‐vivo imaging probes and diagnostics without prior knowledge of target enzymes. This has the potential to be applied to diverse disease states using clinical or animal‐model tissue samples.